PENGARUH NPL, CAR, INFLASI, SUKU BUNGA DAN KURS MELALUI JUMLAH PENYALURAN KREDIT TERHADAP PROFITABILITAS PERBANKAN - Reza Zattira (STIE Mandala Jember, 2016)
This study was conducted to examine the effect of Non-Performing Loans(NPL), Capital Adequacy Ratio (CAR), inflation, interest rates and exchange ratethrough credit expansion to profitability of banks. The samples are ten biggest assetbanking company's in Indonesia in 2011-2014, using purposive sampling technique.This research method by using path analysis or path analysis. Test the hypothesis byusing statistical t-test to test the partial coefficients, as well as statistical F test todetermine the effect of jointly using a 5% significance. It also made the classicassumption test including normality test, multicollinearity test, heteroscedasticity testand autocorrelation test. During the period show that the study data were normallydistributed. Based normality test, multicollinearity, heteroscedasticity test andautocorrelation test found no deviation from the classical assumptions. The resultsshowed that the variable NPL has a negative influence significantly to amount oflending, but CAR, sensitivity of interest rate, sensitivity of inflation, sensitivity ofexchange rate have no effect on the amount of lending. In addition the results of thisstudy indicate that the NPL, CAR, of interest rate, sensitivity of inflation, sensitivityof exchange rate have no effect on ROA, besides the amount of lending has positiveeffect on profitability of ROA.